Assessing investment strategies in mining projects in the Asia-Pacific region - Foo, Nam Yoke (Curtin University, 2015)
The Asia-Pacific region has experienced a significant period of development over the last four decades. Rapid urbanisation has resulted in an increased demand for mineral resources indicating the resource industry has contributed the primary income to the economies of many Asia-Pacific countries. The objective of this thesis is to shed light on investment opportunity using the strategy of timing flexibility. This thesis uses two methodologies, namely Net Present value (NPV) and real options valuation (ROV), to conduct an investment analysis assessing timing flexibility. This thesis finds that commodity prices affect the mining investors’ decisions. However, the impact of tax policy uncertainty is quite subtle.